2017
DOI: 10.1038/ni.3728
|View full text |Cite
|
Sign up to set email alerts
|

A self-sustained loop of inflammation-driven inhibition of beige adipogenesis in obesity

Abstract: In obesity, white adipose tissue (AT) inflammation is associated with reduced beige adipogenesis, a thermogenic and energy-dissipating function mediated by uncoupling protein-1 (UCP1)-expressing beige adipocytes. Here, we dissected an inflammation-driven inhibitory mechanism of beige adipogenesis in obesity that required direct adhesive interactions between macrophages and adipocytes mediated, respectively, by α4 integrin and its counter-receptor VCAM-1, the expression of which was upregulated in obesity. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 65 publications
(117 reference statements)
5
135
0
Order By: Relevance
“…Alternatively activated macrophages have been proposed to promote adaptive thermogenesis directly via their production of catecholamines (Nguyen et al, 2011), although independent studies found that adipose tissue macrophages from cold-exposed mice do not express the key catecholamine synthesis enzyme tyrosine hydroxylase (TH) (Chang et al, 2016; Fischer et al, 2017; Spadaro et al, 2017), and TH deletion in hematopoietic cells neither affected adipose tissue browning nor energy expenditure in response to cold (Fischer et al, 2017). In contrast, polarization towards a more proinflammatory activation directly inhibits adipose tissue browning (Chung et al, 2017) and in turn, browning has been described to limit adipose tissue inflammation (Cohen et al, 2014). However, regardless of whether macrophages directly promote thermogenesis, all of these studies confirm the presence of immune cells resident in adipose tissue in homeostatic and adaptive settings.…”
Section: Innate Immune Cellular Mediators Of Inflammationmentioning
confidence: 99%
“…Alternatively activated macrophages have been proposed to promote adaptive thermogenesis directly via their production of catecholamines (Nguyen et al, 2011), although independent studies found that adipose tissue macrophages from cold-exposed mice do not express the key catecholamine synthesis enzyme tyrosine hydroxylase (TH) (Chang et al, 2016; Fischer et al, 2017; Spadaro et al, 2017), and TH deletion in hematopoietic cells neither affected adipose tissue browning nor energy expenditure in response to cold (Fischer et al, 2017). In contrast, polarization towards a more proinflammatory activation directly inhibits adipose tissue browning (Chung et al, 2017) and in turn, browning has been described to limit adipose tissue inflammation (Cohen et al, 2014). However, regardless of whether macrophages directly promote thermogenesis, all of these studies confirm the presence of immune cells resident in adipose tissue in homeostatic and adaptive settings.…”
Section: Innate Immune Cellular Mediators Of Inflammationmentioning
confidence: 99%
“…Adhesion was performed as previously described with modifications (29,76,77). Nunc-Immuno MicroWell 96-well solid plates (Sigma-Aldrich) were coated overnight at 4°C with Del-1-Fc (10 μg/ml) and washed twice with PBS, and blockade was performed with 1% BSA in PBS for 1 hour.…”
Section: Cell Cycle Analysis Of Lt-hscs From Edil3mentioning
confidence: 99%
“…Microglia cells were isolated from Hif2a-HWT and Hif2a-HKO mice according to previously described protocols (27,28). Bone marrow-derived macrophages (BMDM) were isolated according to previously described protocols (29,30).…”
Section: Cell Culturementioning
confidence: 99%